STRATEGI KOMUNIKASI REMAJA MASJID SYUHADA DALAM MELAKUKAN PEMBINAAN AKHLAK REMAJA DI DUSUN MENSEMAT DESA MEKAR JAYA TAHUN 2020 - Jepriadi; Azwar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Islamic preaching is an activity of communicating the teachings of Allah Almighty which are contained in the Al-Quran and Sunnah, so that people can take it as their way of life. Given the many problems that occur among adolescents, ranging from moral and moral crises. To overcome this problem, of course there is a training that is carried out. In the process of coaching adolescents, special abilities are needed. One of them is the communication strategy carried out in the youth coaching process. The purpose of this study in general is to find out the communication strategies of the Syuhada mosque youth in conducting adolescent morals development in the Mensemat Hamlet, Mekar Jaya Village. Whereas specifically, knowing the communication planning and communication management carried out by the teenagers of the Syuhada mosque in developing youth morals in the Dusun Mensemat, Mekar Jaya Village, and knowing the supporting and inhibiting factors for the success of the Syuhada mosque youth communication strategy in developing youth morals in the Mensemat Village Mekar Jaya Village. This type of research is descriptive qualitative research. In this study, the data consisted of primary and secondary data. The data collection techniques are observation, interview, and documentation techniques. The data analysis technique used was data reduction, data presentation, verification and conclusion drawing. After being analyzed, the validity of the data is tested by mamber check, and triangulation. The conclusions of the results of the research ari: Communication planning carried out by teenagers of the Syuhada mosque in adolescent moral development in Menemat Village, Mekar Jaya Village is in the form of determining activities in adolescent morality development, determining messages to provide guidance, and selecting media in the process of building morals for adolescents, Communication management that is carried out is planning and evaluating the communication strategy undertaken. Supporting factors and obstacles to the success of the Syuhada Mosque youth communication strategy are in the form of external and internal Tractors including adequate facilities and infrastructure, inadequate use of time, adolescents who are difficult to provide guidance, poor signal quality in conveying messages, and parents.